\(\displaystyle{f{{\left({x}\right)}}}={\cos{{\left({2}{x}+{7}\right)}}}\)

\(\displaystyle{f{{\left({x}\right)}}}=-{\sin{{\left({2}{x}+{7}\right)}}}\dot{{\lbrace}}{\frac{{{d}}}{{{\left.{d}{x}\right.}}}}{\left({2}{x}+{7}\right)}\), u=2x+7

\(\displaystyle=-{\sin{{\left({2}{x}+{7}\right)}}}\dot{{\lbrace}}{2}\)

\(\displaystyle=-{2}{\sin{{\left({2}{x}+{7}\right)}}}\)

\(\displaystyle{f{{\left({x}\right)}}}=-{\sin{{\left({2}{x}+{7}\right)}}}\dot{{\lbrace}}{\frac{{{d}}}{{{\left.{d}{x}\right.}}}}{\left({2}{x}+{7}\right)}\), u=2x+7

\(\displaystyle=-{\sin{{\left({2}{x}+{7}\right)}}}\dot{{\lbrace}}{2}\)

\(\displaystyle=-{2}{\sin{{\left({2}{x}+{7}\right)}}}\)